1997
DOI: 10.1002/etc.5620160803
|View full text |Cite
|
Sign up to set email alerts
|

Initial sorption of aromatic amines to surface soils

Abstract: Sorption of aniline, α‐naphthylamine, and benzidine to three silty clay loams was measured from CaCl, electrolyte solutions in single and binary solute systems after a 1‐d residence time. Soils varied in pH (4.4–7.2), cation‐exchange capacity (CEC, 10–30 cmolc/kg), and organic carbon content (OC, 1–3%). Plots of sorbed amine concentrations versus aqueous amine concentrations exhibited nonlinearity in the concentration range investigated. Sorption increased with decreasing soil‐solution pH for all solutes. Decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…The loss of these compounds is unlikely due to microbial metabolism since the soil was sterilized by ovenheating (105 C). These findings are consistent with numerous reports of amines adsorbing to clay material in soil (Zhang et al, 1993;Lee et al, 1997) as well as other metabolites, especially carboxylic acids, potentially forming covalent bonds with organic matter or being chelated by metals or other ions (originating from soil or from the extractant) (Jones et al, 2003;Fischer et al, 2010). Therefore, cationic compounds such as polyamines may represent an inaccessible biological class of substrates that are not present in DOM in situ.…”
Section: Some Microbial Metabolites Rapidly Adsorb To Soilsupporting
confidence: 93%
“…The loss of these compounds is unlikely due to microbial metabolism since the soil was sterilized by ovenheating (105 C). These findings are consistent with numerous reports of amines adsorbing to clay material in soil (Zhang et al, 1993;Lee et al, 1997) as well as other metabolites, especially carboxylic acids, potentially forming covalent bonds with organic matter or being chelated by metals or other ions (originating from soil or from the extractant) (Jones et al, 2003;Fischer et al, 2010). Therefore, cationic compounds such as polyamines may represent an inaccessible biological class of substrates that are not present in DOM in situ.…”
Section: Some Microbial Metabolites Rapidly Adsorb To Soilsupporting
confidence: 93%
“…Assuming cation exchange as the primary sorption mechanism and that each ionic species has its own sorption magnitude, similar to what has been done for other ionizable compounds on soils (36) and for OTC and TC on pure clays (19), the following weighted sum model was employed:…”
Section: Resultsmentioning
confidence: 99%
“…The different sorption behavior of AN and NA was also discussed by Li et al (2001) and Lee et al (1997). The authors observed that both, degree of nonlinearity and magnitude of sorption, were less for AN relative to NA.…”
Section: Kinetic Sorption Conceptsmentioning
confidence: 88%